Effective Debriefing Helps Achieve Learning Objectives in the Classroom (Journal of Education and Educational Development, 2020)
Learning involves making sense of whatever has been taught or experienced in the classroom (Watkins, 2009). Individual students may, in fact, interpret such experiences of learning differently and may apply this knowledge distinctly throughout their lives. Classroom activities in this regard may work as useful tools to enhance students’ learning experiences through active involvement and reflective practices (Watkins, 2009). However, if whatever done in the class makes no sense to a student and is not integrated effectively with the content and students’ demographics both purpose and process of teaching and learning become ambiguous (Berman, 2004). One of the many reasons where studentslearning is said to be hampered is inadequate opportunity left for the teacher to debrief or review activities once they are done (Dennison, & Kirk, 1990). Thus, I believe, one of the ways to ensure student learning is adequate integration of pedagogy with learning objectives through reviewing and debriefing exercises.